PERAN MAHASISWA DALAM INOVASI DAN PEMASARAN STICK LABU KUNING DI DESA MEKAR INDAH - Marsiah, Marsiah; Wati, Zahwa Karunia; Alamsyah, Fikry; Ninsy, Rauhunt Octavia; Rahman, Abdul; Vita, Vita; Umam, Nurul; Rajudin, Rajudin; Febriani, Aulia Ananda; Maulana, Rahmat; Khatimah, Husnul (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Pumpkin is a type of plant that is high in nutritious content and can be put into a variety of preparations, one of which is pumpkin sticks produced in collaboration with the community by the Mekar Indah Village PKK organization. The challenges include a lack of innovation in flavor variants in creating pumpkin sticks, as well as the product not being generally known outside of the hamlet. This service project seeks to bring flavor innovation in pumpkin sticks as well as introduce it to individuals living outside of Mekar Indah Village, Seruyan Regency. This community service project employs Asset Based Community Development (ABCD). This activity creates new flavor versions of pumpkin stick products that are in high demand in the community, and the items are known and promoted outside of Mekar Indah Village to benefit local residents' economies.